Design and Development of a UVC Ray Disinfection System for Personal Protective Equipment in High-Demand Facilities - Razuri-Madrid, A.; Morales-Moisela, M.M.; Balcazar, M.; Gonzales Carazas, M.M.; Casado, F.L.; Flores, A. (Springer Science and Business Media Deutschland GmbH, 2025)
Since the latest pandemic, there is an increased demand for personal protective equipment (PPE) such as N95 masks, creating shortages. As a result, the need arises to disinfect and reuse PPE, with UVC ultraviolet radiation being a promising method. The objective was to design and build UVC disinfection equipment for N95 masks that guarantees their effective reuse. A prototype was made for biological validation with Bacillus subtilis and microscopic analysis of fibers in 3 cycles of 5 min of UVC. The final equipment for 32 masks was then built in 5 min according to validated parameters. The results showed that 5 min of UVC significantly reduced the microbial load without affecting the masks. Repetitive irradiation should not exceed 3 cycles. It is concluded that functional equipment was obtained whose parameters guarantee the effective disinfection of N95 masks in the face of the health emergency.
Keywords: Personal protective equipment; On demand; Business; Engineering; Architectural engineering; Medicine; Commerce; Pathology; Coronavirus disease 2019 (COVID-19); https://purl.org/pe-repo/ocde/ford#5.02.02